The impact of complaint management and service quality on organizational image: A case study at the Malaysian public university library - Tan P.K.; Mohd Suradi N.R.; Saludin M.N. (2023)
Service failure frequently occurs. This affects customer expectations which lead to complaint. However, not all dissatisfied customers actually complain. Without customer feedback, it would be impossible for a company to know whether they needed a change for improvement. Thus, complaint management brings a learning experience to organization in order to provide better service. Therefore, it is important to identify customer dissatisfaction through a systematic complaint handling or management. The study proposes a model of systematic complaint management which applied to academic library as a tool of service recovery. As such, the main purpose of this study is to investigate the critical success factors of complaint management towards service quality, customer satisfaction, customer loyalty and the impact to organizational image at academic library. Three academic libraries have been identified and selected for this project, the Library of Tun Sri Lanang, UKM, UTeM and UNIMAS. Using the justice theory, this study investigates the perception of customers on complaint management in terms of outcomes they receive, procedures used by organization and interpersonal treatment. In this study, there are five factors of complaint management identified, which includes speed of recovery, management system, empowerment, culture and psychology and tangible compensation. A questionnaire was designed and used as the data gathering instrument. A total of 600 respondents participated in this study. Ten hypotheses were used to test the relationships between complaint management, service quality, customer satisfaction, customer loyalty and organizational image. To measure the construct relationships, Structural Equation Model (SEM) approach was used. The results show that management system (b = 0.210; p < 0.05) exerts the highest positive impact on service quality. It followed by psychology and culture (b = 0.188; p < 0.05), empowerment (b = 0.179; p < 0.05) and tangible compensation (b = 0.175; p < 0.05). However, the empirical results suggest that speed of recovery (b = -0.009; p > 0.05) do not influence service quality. The second part of this study uses confirmatory factor analysis (CFA) to analyze and confirm the conceptual model proposed in this research. The result shows that all the values obtained in this study fits the data reasonably well. 2013 AIP Publishing LLC.